The process parameter effects on hybrid structure of dissimilar materials made by friction stir welding - Hussein, Sadiq Aziz (UTeM, 2016)
In order to accommodate the demand for low weight product, significant effort is being directed towards the replacement of steel by Al Alloys for particular structural parts in transport applications. However, it is difficult to find the most suitable joining method due to dissimilarities in the thermal and mechanical properties of the materials in such structures. For example, joining of Al Alloy to steel by fusion welding methods produces deleterious reactions as a result of the associated melting and resolidification processes. Friction stir welding could be a better choice by exploiting its solid-state process behaviour to join such dissimilar materials. The aim of this study is to investigate the process parameters effect on a joint made by friction stir welding for three dissimilar materials. It also aims to produce this joint in low cost manner, and with modification of tools used. Single pass friction stir welding has been used to join three dissimilar metallic alloys of hardened and tempered Al Alloys in butt configuration, to steel in lap configuration. Preliminary investigation and pilot test have been conducted to achieve low-cost welding process and detect the initial levels of the welding process parameters. Few steps have been implemented to attain suitable range of these parameters of both joints. In Al Alloys to steel joining, diffusion and plunging have been investigated for eligibility, matching with low-cost welding process, and attaining robust joint. The design of experiments and analysis of variance have been used to explain the effects of welding parameters on joint strength in this study. Rule of thumb has been established from preliminary investigation to mitigate the high generated forces during the critical stages of the welding process. This preliminary investigation suggests significant experimental steps for the next stage which is welding of dissimilar materials. The pilot investigation succeeds in detecting the initial level of the welding parameters, selection of best technique for the welding of Al Alloys to steel, and arrangement of Al Alloys sheets on the retreating and advancing sides. The final collected data shows that low welding speed (such as 20 mm/min) is important to attain robust Al Alloy to steel joint, while high speed (such as 300 mm/min) produces high tensile strength of Al Alloys joint. Generally, low rotational speed such as 400-900 rpm, will result in poor weld quality, while high rotational speeds, such as 1800 and 2000 rpm, produce consistent range of joint strengths and good weld quality. Extremely high welding (400 mm/min) and rotational (≥ 2000 rpm) speeds will produce weld defects as well. Steel fragments spattered at the weld zone, weld defects, and the mechanical properties of the formed intermetallic layer and its thickness are the influential factors in the Al Alloy to steel joint. Diffusion technique is known to be able to avoid the limitation of pin plunging into steel. Though the strain failure values may be low as compared to the base materials, dissimilar Al Alloys joint efficiency can achieve 85% of the AA6061-T6 base material, while Al Alloys to steel joints can attain approximately 100% of the steel base material. A new tool, multi-adjustable, has been proposed for the future work. The new design accommodates some of the main affected parameters in the targeted structures as suggested by the final results of this study. The use of this tool could further reduce the cost of the friction stir welding process.